Prenatal clinical manifestations in individuals with COL4A1/2 variants. Issue 8 (30th July 2020) - Itai, Toshiyuki; Miyatake, Satoko; Taguri, Masataka; Nozaki, Fumihito; Ohta, Masayasu; Osaka, Hitoshi; Morimoto, Masafumi; Tandou, Tomoko; Nohara, Fumikatsu; Takami, Yuichi; Yoshioka, Fumitaka; Shimokawa, Shoko; et al.
Abstract : Background: Variants in the type IV collagen gene ( COL4A1/2 ) cause early-onset cerebrovascular diseases. Most individuals are diagnosed postnatally, and the prenatal features of individuals with COL4A1/2 variants remain unclear. Methods: We examined COL4A1/2 in 218 individuals with suspected COL4A1 /2-related brain defects. Among those arising from COL4A1/2 variants, we focused on individuals showing prenatal abnormal ultrasound findings and validated their prenatal and postnatal clinical features in detail. Results: Pathogenic COL4A1/2 variants were detected in 56 individuals (n=56/218, 25.7%) showing porencephaly (n=29), schizencephaly (n=12) and others (n=15). Thirty-four variants occurred de novo (n=34/56, 60.7%). Foetal information was available in 47 of 56 individuals, 32 of whom (n=32/47, 68.1%) had one or more foetal abnormalities. The median gestational age at the detection of initial prenatal abnormal features was 31 weeks of gestation. Only 14 individuals had specific prenatal findings that were strongly suggestive of features associated with COL4A1/2 variants. Foetal ventriculomegaly was the most common initial feature (n=20/32, 62.5%). Posterior fossa abnormalities, including Dandy-Walker malformation, were observed prenatally in four individuals. Regarding extrabrain features, foetal growth restriction was present in 16 individuals, including eight individuals with comorbid ventriculomegaly. Conclusions: Prenatal observation of ventriculomegaly with comorbid foetal growth restriction should prompt a thorough ultrasound examination and COL4A1/2 gene testing should be considered when pathogenic variants are strongly suspected.